PERAN BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU STUDI PADA GURU SMP NEGERI SUB RAYOR 05 KOTA SEMARANG - 11.52.02.0117, Sudjati (Jurnal Mahasiswa Pasca Sarjana, 2013)
The objective of the study is to examine and to analyse the role of organization culture and principal transformational leadership moderate the effect of work motivation on teacher performance in SMP Negeri Sub Rayon 05 Kota Semarang.The respondents of the study were 161 teachers of SMP Negeri Sub Rayon 05 Kota Semarang (SMPN 4, SMPN 6, SMPN 20, and SMPN 38). The primary data were collected by using questionnaire which consist of 65 indicators measuring variables of the study. This study used regression analysis.The findings of the study by using factor analysis revealed that work motivation, culture organization, and principal transformational leadership had positive and significant effect on teacher performance. However, culture organization and principal transformational leadership did not moderate the effect of work motivation on teacher performance. Key words: Work Motivation, Culture Organization, Principal Transformational Leadership, Teacher Performance.